Gram-Scale Synthesis of the Co(nmp)2 Catalyst to Prepare trans-2,5-Disubstituted Tetrahydrofurans by the Aerobic Oxidative Cyclization of Pent-4-en-1-ols - Morra, Barbora; Morra, Nicholas A.; MacDonald, Daniel G.; Pagenkopf, Brian L. (Synthesis, 2020)
Co(nmp)2 is an efficient catalyst for the aerobic oxidative cyclization of pent-4-en-1-ols to give 5-hydroxymethyl trans-tetrahydrofurans (THFs) as single diastereomers in high yield. The trans-THF pharmacophore is of interest because it is found in many biologically active natural products. The three-step synthesis of Co(nmp)2 described here gives the catalyst as a fine powder in 80–85% overall yield on 10-gram scale. The use of the catalyst in a representative oxidative cyclization is also described.
Keywords: catalysis; cyclization; furans; green chemistry; heterocycles; ligands; oxygenations; stereoselective synthesis